TFAP2E-DKK4 and chemoresistance in colorectal cancer - Ebert, Matthias; Tänzer, Marc (The New England journal of medicine, 2012)
To the Editor: Ebert et al. (Jan. 5 issue)1 report that hypermethylation of the gene encoding transcription factor AP-2 epsilon (TFAP2E) reduces its expression and is associated with chemoresistance in patients with colorectal cancer and in colorectal-cancer cell lines in vitro. The test has dramatic clinical value: the response rate increased from less than 15% among hypomethylated tumors to more than 80% among hypermethylated tumors. Methylation of this gene had a huge biologic and clinical effect. However, we have several questions. First, the methylation status differs between primary tumors and metastases in approximately 30% of tumors: were these tumors considered . . .
Gesehen am 16.04.2019